A Qualitative Study of Technology Integration into Culture and Sustainability in Schools. (9th April 2013) - Mundy, Marie-Anne; Kupczynski, Lori
Abstract : Despite overall increased access to technology both in and out of the classroom, technology is often still not being used to support learning and instruction in a meaningful manner. Teachers need to be helped to change the way they teach rather than just how to use computers. The TeachUp! Program was designed by Digital Opportunity Trust to improve the use of technology in day-to-day teaching activities through the use of interns who are present in the schools as a continuous support system and who provide an informal professional development. Interns examine types of technology available and how it can be utilized as a part of the design and implementation of the curriculum to extend the existing student knowledge and learning. Purposive samples from two school districts in southern Mississippi were selected to be interviewed on their perceptions of the integration of TeachUp! technology empowerment into the ongoing culture and operation of the schools, long-term systematic change, and improvement in education outcomes. According to the respondents, the TeachUp! Program has had a major sustaining effect on the respective school systems in these areas. The climate of the learning environment has evolved into a true 21st century learning organization with an increase in the use of technology.